1993
DOI: 10.1021/bi00056a001
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a novel specificity in subtilisin BPN'

Abstract: The specificity of subtilisin BPN' toward substrates with large hydrophobic P4 residues has been improved by single amino acid replacements at positions 104 and 107. Mutations were designed to (i) increase the size of the P4 binding pocket by replacing Ile107, which is at the bottom of the S4 pocket, by Val, Ala, and Gly and (ii) lose the hydrogen bond between Tyr104 and Ser130 at the entrance of the P4 binding pocket by changing Tyr104 to Phe and thus reduce interactions between small P4 side chains and resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 32 publications
1
60
0
Order By: Relevance
“…Based on these structural studies, several groups have mutated the S 4 pocket in an attempt to alter the P 4 substrate specificity of subtilisin (21)(22)(23)(24)(25)(26). Wells and co-workers (27,28) found that substitutions of Asp for Tyr 104 in subtilisin BPNЈ increased cleavage of substrates containing a P 4 Arg, but the resulting mutant protease did not discriminate between Arg and Phe at this position.…”
mentioning
confidence: 99%
“…Based on these structural studies, several groups have mutated the S 4 pocket in an attempt to alter the P 4 substrate specificity of subtilisin (21)(22)(23)(24)(25)(26). Wells and co-workers (27,28) found that substitutions of Asp for Tyr 104 in subtilisin BPNЈ increased cleavage of substrates containing a P 4 Arg, but the resulting mutant protease did not discriminate between Arg and Phe at this position.…”
mentioning
confidence: 99%
“…Like in mesentericopeptidase, a threonine residue is located at position 130 in subtilisin RT-5, in contrast to Ser 13° in all other subtilisins. This Ser 13° is involved in hydrogen-bonding with Tyr TM at the entrance of the P4-binding pocket [3]. Mutations to remove this H bond and to increase the size of the S4-binding pocket resulted in a mutant enzyme with increased catalytic efficiency for large hydrophobic residues at position P4 [3].…”
Section: Discussionmentioning
confidence: 99%
“…This Ser 13° is involved in hydrogen-bonding with Tyr TM at the entrance of the P4-binding pocket [3]. Mutations to remove this H bond and to increase the size of the S4-binding pocket resulted in a mutant enzyme with increased catalytic efficiency for large hydrophobic residues at position P4 [3]. The increased preference of subtilisin RT-5 toward hydrophobic residues like valine and phenylalanine at the P4 position may, therefore, correlate with the substitution of Ser 13° to Thr 13°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the trypsin specifi city is mainly determined by the single large S1-binding site selective for Arg or Lys, the specifi city of the subtilisin is rather broad and is determined by the two S1-and S4-binding sites (Wright et al , 1969 ). Due to the wide industrial use of subtilisin, there were numerous attempts to modify its specifi city (Rheinnecker et al , 1993(Rheinnecker et al , , 1994Takagi et al , 1997 ).…”
Section: Inhibition Of the S8 Family Serine Proteasesmentioning
confidence: 99%